Synergistic inhibition of zinc corrosion by some anions in aqueous media - El-Gaber,A.S. (2008)
The corrosion inhibition of zinc in 0.1M HCl in presence and absence of some hydrazide derivatives has been investigated using mass-loss and polarization techniques. Results obtained showed that the inhibition efficiency increased with the increase of the concentration of the additives and decreased with the increase of temperature. Synergism between I- , SCN- and Br- anions and hydrazide derivatives was proposed. The polarization curves showed that hydrazide derivatives act as mixed-type inhibitors, acting predominantly as cathodic inhibitors for zinc in 0.1M HCl .The adsorption of these hydrazide derivatives on zinc surface follows Temkins adsorption isotherm. Some thermodynamic parameters were calculated. The kinetic parameters of corrosion of zinc in HCl solution have been studied.